A Drop of Blood: Newborn Heel Blood Screening Programmes, Innovations, and Contrary Voices in Türkiye and The World - Karagöz, Melek İpek; Gafarlı, Laman; Barutçu, Adnan (Scientific Reports in Medicine, 2025)
Congenital metabolic diseases are mostly autosomal recessive diseases that can be detected in the neonatal period and can lead to disability and even death if left untreated. Screening programmes for early diagnosis are organised worldwide to prevent such diseases. Heel Blood Screening (HBS), which is widely used in Türkiye and in the world, is an example of this. In our country in Türkiye, HBS is performed for phenylketonuria, biotidinase deficiency, cystic fibrosis, hypothyroidism, adrenal hyperplasia and spinal muscular atrophy. However, in recent years there has been opposition to heel prick screening among some people for different reasons. For families, navigating the abundance of available health information and making informed decisions is becoming increasingly complex. Today, when the influence of the media is stronger than ever, parents are exposed to so much information, opinions and messages about what they ‘should’ or ‘should not’ do about their children’s health that it is difficult to distinguish right from wrong.